The Nature and Catalytic Function of Cation Sites in Zeolites: a Computational Perspective - Li, Guanna; Pidko, Evgeny A. (ChemCatChem, 2019)
Zeolites have a broad spectrum of applications as robust microporous catalysts for various chemical transformations. The reactivity of zeolite catalysts can be tailored by introducing heteroatoms either into the framework or at the extraframework positions that gives rise to the formation of versatile Brønsted acid, Lewis acid and redox‐active catalytic sites. Understanding the nature and catalytic role of such sites is crucial for guiding the design of new and improved zeolite‐based catalysts. This work presents an overview of recent computational studies devoted to unravelling the molecular level details of catalytic transformations inside the zeolite pores. The role of modern computational chemistry in addressing the structural problem in zeolite catalysis, understanding reaction mechanisms and establishing structure‐activity relations is discussed. Special attention is devoted to such mechanistic phenomena as active site cooperativity, multifunctional catalysis as well as confinement‐induced and multisite reactivity commonly encountered in zeolite catalysis. Caught in the midst of complexity: This Review presents an overview of recent computational studies on catalysis by cation‐modified zeolites. The role of computational chemistry in addressing the structural and mechanistic complexity underlying the catalytic function of these system is discussed. The multifunctional and multisite dynamic reactive environments need to be explicitly accounted for in computational models to enable derivation of predictive structure‐activity relations in zeolite catalysis.